PUBLIC FIRM'S BACKGROUND ON THE PERFORMANCEGOVERNANCE RELATION: EVIDENCE FROM INDONESIA - Kusdhianto Setiawan; Eddy Junarsin; Sri Handaru Yuliati (Faculty of Economics and Business, Universitas Gadjah Mada, 2013)
This study purports to test two governance issues in Indonesian listed firms. To explore corporategovernance mechanisms in Indonesia, we ought to understand that listed firms on theIndonesian capital market came from two initial business backgrounds: (1) private firms, whichhad been private businesses before going public; and (2) Badan Usaha Milik Negara (stateownedenterprises), which were owned by the Indonesian government and managed bygovernment-appointed management. Although both types of the firms have gone public, theirdifferences might remain intact, such as differences in size, lines of business, market share, andthe efficiency of corporate governance. Using 442 raw sample from all firms listed on theIndonesian Stock Exchange during 2003-2012, we find that governance characteristics andperformance relation does differ between previously SOE firms and previously private firms.However, we do not find evidence of distinct financial performance between previously SOEfirms and previously private firms.1 Corresponding author. We are grateful for the researchgrant provided by the Faculty of Economics and Business,Universitas Gadjah Mada.Keywords: SOE firms, private firms, corporate governance, firm performance, firm background